Edge Version of Metric Dimension and Doubly Resolving Sets of the Necklace Graph - Jia-Bao Liu; Zohaib Zahid; Ruby Nasir; Waqas Nazeer (Mathematics, 2018)
Consider an undirected and connected graph <semantics> G = ( V G , E G ) </semantics> , where <semantics> V G </semantics> and <semantics> E G </semantics> represent the set of vertices and the set of edges respectively. The concept of edge version of metric dimension and doubly resolving sets is based on the distances of edges in a graph. In this paper, we find the edge version of metric dimension and doubly resolving sets for the necklace graph.